2013
DOI: 10.1063/1.4820460
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation blocking by AlGaN hot electron injecting layer in the epitaxial growth of GaN terahertz Gunn diode

Abstract: This paper reports an efficient method to improve the crystal quality of GaN Gunn diode with AlGaN hot electron injecting layer (HEI). An evident reduction of screw dislocation and edge dislocation densities is achieved by the strain management and the enhanced lateral growth in high temperature grown AlGaN HEI layer. Compared with the top hot electron injecting layer (THEI) structure, the bottom hot electron injecting layer (BHEI) structure enhances the crystal quality of transit region due to the growth sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Lee et al showed in [9] that the Gunn diode with 550 nm transit length is capable to achieve a 500 GHz signal of 2.61 W with 2.27% efficiency under 22 V DC and 5 V RF condition. In [10], an efficient method to improve the crystal quality of GaN Gunn diode with AlGaN hot electron injecting layer on SiC substrate was reported. Multi-channel Gunn diode, which is realized by containing multiple AlGaN/GaN heterostructures as GaN-based HEMT-like planar Gunn diode improves the output power and the characteristics at a higher frequency, was proposed in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al showed in [9] that the Gunn diode with 550 nm transit length is capable to achieve a 500 GHz signal of 2.61 W with 2.27% efficiency under 22 V DC and 5 V RF condition. In [10], an efficient method to improve the crystal quality of GaN Gunn diode with AlGaN hot electron injecting layer on SiC substrate was reported. Multi-channel Gunn diode, which is realized by containing multiple AlGaN/GaN heterostructures as GaN-based HEMT-like planar Gunn diode improves the output power and the characteristics at a higher frequency, was proposed in [11].…”
Section: Introductionmentioning
confidence: 99%